Understanding self-directed learning in the context of mobile Web 2.0 – case study with workplace learners. Issue 2 (17th February 2016) - Gu, Jia
ABSTRACT: This paper presents the findings from a multiple-case study which has investigated the impact of mobile Web 2.0 technologies on self-directed learning (SDL) of workplace learners by exploring participants' learning experiences with a mobile App. Drawing on existing literatures, we examined learners' SDL personal attributes and process in the context of mobile Web 2.0. Results show that there are specific personal attributes that could benefit from features of the latest mobile Web 2.0 technologies. These features were utilized increasingly during the learning process and appear to have the potential to enhance learning outcomes. The findings within five individualized cases of adult learners in China using mobile phones for informal learning are provided, followed by a discussion of the overall context. Directions for future development are suggested at the end of the paper.